2017
DOI: 10.3390/v9030056
|View full text |Cite
|
Sign up to set email alerts
|

Complete and Incomplete Hepatitis B Virus Particles: Formation, Function, and Application

Abstract: Hepatitis B virus (HBV) is a para-retrovirus or retroid virus that contains a double-stranded DNA genome and replicates this DNA via reverse transcription of a RNA pregenome. Viral reverse transcription takes place within a capsid upon packaging of the RNA and the viral reverse transcriptase. A major characteristic of HBV replication is the selection of capsids containing the double-stranded DNA, but not those containing the RNA or the single-stranded DNA replication intermediate, for envelopment during virion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
245
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(257 citation statements)
references
References 101 publications
4
245
0
Order By: Relevance
“…The current speculations include the immature RNAcontaining virion as a byproduct of normal HBV replication and exosome secretion (20). The current study data showed that the serum HBV RNA level was positively correlated with serum ALT and AST levels ( Figure 2).…”
mentioning
confidence: 51%
“…The current speculations include the immature RNAcontaining virion as a byproduct of normal HBV replication and exosome secretion (20). The current study data showed that the serum HBV RNA level was positively correlated with serum ALT and AST levels ( Figure 2).…”
mentioning
confidence: 51%
“…Inside the capsid, the polymerase converts pgRNA into rcDNA through reverse transcription, followed by envelopment by HBV envelope proteins on the endoplasmic reticulum membrane for virion secretion through multivesicular bodies, or reentry into the nucleus to replenish the cccDNA pool. In addition to rcDNA, HBV reverse transcription produces a minor viral DNA species, double‐stranded linear DNA (dslDNA), which can be secreted as virion DNA and redirected into the nucleus to form cccDNA . However, dslDNA is often randomly integrated into the host genome through nonhomologous end joining, which may promote HCC development by inducing chromosomal instability, insertional mutagenesis of HBV genes, and HCC‐associated host genes .…”
Section: Serum Hbv Rna In the Viral Life Cyclementioning
confidence: 99%
“…The production of empty virus can be induced by S protein alone while L protein is not necessary but can promote the secretion of empty virus, which may be one of the reasons why empty virus (10 11 IU/mL) are much more than complete virus (10 9 IU/mL) . The L protein, also located in the envelope of empty virus, can help virus enter hepatocytes like a mature Dane particle through sodium taurocholate cotransporting polypeptide (NTCP) receptor and regulate HBV re‐infection, or extracellularly, neutralize the anti‐HBs . The components, HBcAg and HBsAg, of empty virus might be the mirror of HBV replication and immune status.…”
Section: Application Of Viral Markers In Chb Clinical Practicementioning
confidence: 99%